Critical Factors Influencing the Bid / No-Bid Decision in the Palestinian Construction Industry - Mahamid, I. (Engineering, Technology & Applied Science Research, 2022)
The purpose of this study is to identify and rank the factors influencing the bid/no-bid decision according to their relative importance from the perspective of the contractors in the West Bank in Palestine. To achieve the study objectives, a questionnaire survey was conducted. The survey covered a randomly selected sample of 64 contractors involved in the construction industry in the West Bank. The questionnaire’s structure is based on the related literature, the pilot study, and the feedback from local experts in the construction industry. A total of 32 factors that might influence the bid/no-bid decision were identified and considered. Then, the targeted population was asked to rank these factors according to their relative importance. The results indicate that the top five factors affecting a contractor’s decision to bid or not include the financial stability of the client, the identity and reputation of the client in the industry, the promptness of the client in the payment process, the expected profitability, and the project’s source of funding. On the other hand, the least affecting factors are the type of the project, client’s requirements, taxes, laws and government regulations, and weather conditions. The paper provides a comprehensive understanding of the factors affecting the bidding decision. Construction parties and researchers could benefit from the results of this study.